Odpowiedź:
Szczegółowe wyjaśnienie:
a=4[tex]\sqrt{3}[/tex]
a/2=2[tex]\sqrt{3}[/tex]
a=30
V=1/3Pp*H
Ppc=Pp+4Pb
H/(a/2)=tg30
H=(a/2)*tg30
H=2[tex]\sqrt{3}[/tex]*([tex]\sqrt{3}[/tex]/3)=2 cm
Pp=a^2
Pp=(4[tex]\sqrt{3}[/tex])^2=48 cm^2
V=1/3Pp*H=1/3*48*2=32 cm^3
Pb=1/2a*h
(a/2)/h=cos30
h=a/2cos30
h=4[tex]\sqrt{3}[/tex]/(2*4[tex]\sqrt{3}[/tex]/2)=4[tex]\sqrt{3}[/tex]/[tex]\sqrt{3}[/tex]=4 cm
Pb=1/2*4[tex]\sqrt{3}[/tex]*4=8[tex]\sqrt{3}[/tex]
Ppc=48+4*8[tex]\sqrt{3}[/tex]=48+32[tex]\sqrt{3}[/tex]
Ppc=16(3+2[tex]\sqrt{3}[/tex])cm^2